2023
DOI: 10.3390/genes14081517
|View full text |Cite
|
Sign up to set email alerts
|

Brain Targeted AAV1-GALC Gene Therapy Reduces Psychosine and Extends Lifespan in a Mouse Model of Krabbe Disease

Abstract: Krabbe disease (KD) is a progressive and devasting neurological disorder that leads to the toxic accumulation of psychosine in the white matter of the central nervous system (CNS). The condition is inherited via biallelic, loss-of-function mutations in the galactosylceramidase (GALC) gene. To rescue GALC gene function in the CNS of the twitcher mouse model of KD, an adeno-associated virus serotype 1 vector expressing murine GALC under control of a chicken β-actin promoter (AAV1-GALC) was administered to newbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Gene therapy using adeno-associated viruses (AAVs) [ 73 , 74 ] has several advantages over lentiviruses, including a broader tropism for CNS cell populations and the ability to cross the blood–brain barrier (for specific serotypes). An AAV1-GALC gene therapy study demonstrated reduced psychosine levels in the brain of a mouse model, indicating that delivery of the viral vector via the cerebroventricular system can decrease the rate of the disease progression in Krabbe disease [ 75 ]. Another study using a viral vector carrying the ASPA gene in patients with Canavan disease demonstrated safety and resulted in some clinical benefits [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy using adeno-associated viruses (AAVs) [ 73 , 74 ] has several advantages over lentiviruses, including a broader tropism for CNS cell populations and the ability to cross the blood–brain barrier (for specific serotypes). An AAV1-GALC gene therapy study demonstrated reduced psychosine levels in the brain of a mouse model, indicating that delivery of the viral vector via the cerebroventricular system can decrease the rate of the disease progression in Krabbe disease [ 75 ]. Another study using a viral vector carrying the ASPA gene in patients with Canavan disease demonstrated safety and resulted in some clinical benefits [ 76 ].…”
Section: Introductionmentioning
confidence: 99%